Age-Related Disparities in the Treatment of Borderline/Mild Hearing Loss in the United States. Issue 1 (March 2022) - Grewal, Maeher; Dragon, Jacqueline; Golub, Justin S.
To investigate disparities in hearing aid use across the life span for borderline/mild hearing loss, a cross-sectional epidemiologic study in the National Health and Nutrition Examination Survey was conducted. Multivariable logistic regressions controlling for hearing level analyzed the association between hearing aid use and age in borderline/mild hearing loss. Age was grouped into quartiles. Of 2470 subjects, 2.0% (n = 50) were <25 years old; 12.0% (n = 297), 25 to 49 years; 65.5% (n = 1618), 50 to 74 years; and 20.5% (n = 505), ≥75 years. When compared with the youngest quartile and while controlling for hearing level, those in the second quartile were 4.6 times less likely to use hearing aids ( P < .01); those in the third were 4.2 times less likely ( P < .01); and those in the fourth were 4.7 times less likely ( P < .001). The dramatically lower hearing aid usage of all older age groups as compared with children/younger adults represents a large unaddressed age-related disparity in the treatment of borderline/mild hearing loss.